On the Long Lasting "C‐Type" Structures in the Sodium Lidargram: The Lifetime of Kelvin‐Helmholtz Billows in the Mesosphere and Lower Thermosphere Region. Issue 4 (30th April 2019) - Mondal, S.; Sarkhel, S.; Agarwal, Jay; Chakrabarty, D.; Sekar, R.; Yuan, Tao; Cai, Xuguang; Liu, Alan Z.; Nozawa, Satonori; Saito, Norihito; Kawahara, Takuya D.; Mlynczak, Martin G.; et al.
Abstract: In order to understand the characteristics of long‐lasting "C‐type" structure in the Sodium (Na) lidargram, six cases from different observational locations have been analyzed. The Na lidargram, collected from low‐, middle‐, and high‐latitude sites, show long lifetime of the C‐type structures which is believed to be the manifestation of Kelvin‐Helmholtz (KH) billows in the Mesosphere and Lower Thermosphere (MLT) region. In order to explore the characteristics of the long‐lasting C‐type structures, the altitude profile of square of Brunt‐Väisälä frequency in the MLT region has been derived using the temperature profile collected from the Na lidar instruments and the SABER instrument onboard TIMED satellite. It is found to be positive in the C‐type structure region for all the six cases which indicates that the regions are convectively stable. Simultaneous wind measurements, which allowed us to calculate the Richardson numbers and Reynolds numbers for three cases, suggest that the regions where the C‐type structure appeared were dynamically stable and nonturbulent. This paper brings out a hypothesis wherein the low temperature can increase the magnitude of the Prandtl number and convectively stable atmospheric region can cause the magnitude of Reynolds number to decrease. As a consequence, the remnant of previously generated KH billows in nearly "frozen‐in" condition can be advected through this conducive region to a different location by the background wind where they can sustain for a long time without much deformation. These long‐lived KH billows in the MLT region will eventually manifest the long‐lasting C‐type structures in the Na lidargram. Key Points: The stability of KH billows in the MLT region on Reynold number and Prandtl number on long‐lasting "C‐type" structure in the Na lidargram Low temperature can increase magnitude of Prandtl number and convectively stable atmosphere can decrease the magnitude of Reynolds number This conducive atmosphere is responsible for the long lifetime of the remnant of previously generated KH billows in the MLT region